Rapıd Maxıllary Expansıon - İlken Kocadereli (Galenos Yayinevi, 1996)
On this article the effects of rapid maxillary expansion on facial structures and dentition are reviewed. The patient age, RME indications, force application and residuel loads, retetion and relaps, surgical RME applications, nasal airway changes are discussed.